The Influence of Principal Leadership on Teacher Performance - Budi Suhartono; Hariyani Hariyani (Journal of Leadership, Organization, Vision, and Administration, 2025)
This study aims to determine the influence of principal leadership on the performance of guidance and counseling teachers in secondary schools. A quantitative approach with a correlational design was employed, involving 37 guidance and counseling teachers as respondents. Data were collected using validated leadership and performance questionnaires and analyzed through descriptive statistics and simple linear regression. The findings show that the performance of guidance and counseling teachers falls within the good to very good category, while principal leadership is categorized as fair. The results indicate a significant positive effect of principal leadership on teacher performance. This finding confirms that better principal leadership leads to improved teacher performance in providing counseling services. These results highlight the critical role of effective principal leadership in improving the quality of school counseling services. Therefore, strengthening principals' managerial, supervisory, and motivational competencies is crucial to optimize teacher performance and support the achievement of school counseling goals.